An exploratory randomised trial of a nurse-led telephone support intervention for people who support people with multiple sclerosis (the MNTISS trial) - Corry, Margarita (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2015)
In Ireland, the provision of care by family caregivers contributes substantially to the reduction in annual national expenditure from healthcare budgets. However, the negative impact of providing informal care has been well-documented, with personal and financial cost implications for caregivers. This study focused on the condition of multiple sclerosis and the provision of support to those who provide care to people with multiple sclerosis (PwMS). Although the variety of caregiver support needs require interdisciplinary support, a number of the unmet needs of caregivers of PwMS, such as the need for accurate information and advice, and dealing with the emotional impact of caregiving, can be addressed within the scope of the role of the nurse specialist in multiple sclerosis (NSMS). These nurses have expert knowledge about the PwMS's condition and circumstances, which means they can tailor their support to the individual and the people who support them. Despite the known unmet needs of caregivers of PwMS, there is a dearth of interventions developed and tested to bridge this gap. Therefore, the purpose of this study was to develop and test an intervention to support people who support PwMS (SPs).
Embargo End Date: 2020-06-01
Keywords: Nursing and Midwifery Studies, Ph.D.; Ph.D. Trinity College Dublin, 2015